Local control in sinonasal malignant melanoma: Comparing conventional to hypofractionated radiotherapy. Issue 1 (16th October 2017) - Lansu, Jules; Klop, Willem Martin; Heemsbergen, Wilma; Navran, Arash; Al‐Mamgani, Abrahim; Langendijk, Johannes A.; Kaanders, Johannes H.; Terhaard, Chris; Karakullukcu, Baris; Hamming‐Vrieze, Olga
Abstract: Background: The purpose of this study was to analyze the effect of fractionation schedule on local control in postoperative radiotherapy (RT) for sinonasal malignant melanoma. Methods: Sixty‐three patients who were treated with surgery and postoperative RT in 4 accredited head and neck cancer centers in the Netherlands between 1998 and 2013 were retrospectively studied. Outcomes with conventional fractionation (2‐2.4 Gy per fraction; n = 27) were compared to hypofractionation (4‐6 Gy per fraction; n = 36). The primary endpoint was local control and the secondary endpoint was toxicity. Results: Comparable local control rates were found after 2 and 5 years (63% vs 64% and 47% vs 53%; P  = .73 for, respectively, conventional fractionation vs hypofractionation). Local recurrences were predominantly present ipsilateral (92%) and within the irradiated volume (88%). Late toxicity grade ≥ 3 was observed in 2 of 63 patients, 1 patient in both groups. Conclusion: Radiotherapy fractionation schedule did not influence the local control rate or the incidence of late toxicity in patients treated with surgery and RT for sinonasal malignant melanoma in this retrospective analysis. Due to this retrospective nature and the limited number of patients, strong recommendations cannot be made. Expected toxicity, patient convenience, and workload may be taken into account for the choice of fractionation schedule until conclusive evidence becomes available.